Mapping biodiversity and cultural values complemented with understanding of social dynamics provides effective means for addressing opportunities for nature conservation in a cultural landscape - Morariu, Simona-Diana; Macicasan, Vlad; Malos, Cristian Valeriu; Hartel, Tibor (Frontiers in Environmental Science, 2023)
The ecosystem services framework can usefully complement biodiversity assessments in developing socially robust nature conservation strategies in protected areas and beyond. However, there is still little research, especially in Eastern Europe, which links biodiversity assessment and nature related values to the deeper social-economic dynamics and aspirations existing in the local communities. Here we address this knowledge gap with a study case from Romania. We implemented a biodiversity survey and mapped the protected species and habitats in a Natura 2000 area. Then we used participatory mapping with key local community representatives to understand the type of values linking the local community with the protected area, distinguishing between the past (1960s-1989 period) and present. We identified that socio-economic and cultural values were strong and synergistically manifested in the past but not in the present. A dramatic abandonment of land use practices was reported. The current distribution of protected species and habitats does not overlap with the farmed areas in the past and present. Interviewees report that the local community went through dramatic changes from the past to present: increased individualism, weakened or lost local rules, diversifying individual aspirations, low level of collective actions and weak alignment between knowledge and aspirations and the protected area. New socio-cultural values are represented by educational activities, however, with a lack of genuine local community engagement. Key directions identified by participants for the future of the site were nature-friendly activities such as tourism, biking trails, forestry, and the renewal of viticulture.